A review of magnetic solid catalyst development for sustainable biodiesel production - Krishnan S.G.; Pua F.-L.; Zhang F. (Elsevier Ltd, 2023)
Biodiesel; Catalysts; Effluents; Esterification; Esters; Fossil fuels; Transesterification; Acid catalyst; Alternative source; Base catalyst; Biodiesel production; Esterification reactions; Heterogeneous catalyst; Magnetic solids; Solid catalysts; Transesterification reaction; Transesterifications; Magnetism; biofuel; byproduct; catalysis; catalyst; detection method; effluent; fossil assemblage; fossil fuel; purification; separation; wastewater; wastewater treatment